The effects of an app to prevent negative outcomes of cyberbullying: A cluster randomized controlled trial. - Helene Høgsdal; Sabine Kaiser; Geraldine Mabille; Kyrre Breivik; Frode Adolfsen; Monica Martinussen; Henriette Kyrrestad (PLOS Digital Health)
Experiencing cyberbullying and negative incidents online can negatively affect adolescents' mental health and well-being. NettOpp is a mobile application aiming to reduce the harmful effects of cyberbullying and negative incidents online on mental health outcomes. To evaluate the effect of the mobile app, a cluster randomized controlled trial design with three measurement points was conducted. Thirty-two Norwegian primary and secondary schools were randomly assigned to either an intervention group where the pupils (n = 259) got access to NettOpp during the study period, or to a waiting-list control group where the pupils (n = 327) got access to NettOpp after the study period. No significant findings were found in the intention-to-treat analyses, but the results from per-protocol analyses showed a decrease in hyperactivity problems among the adolescents that had used the app (F(4,1585) = 2.89, p =.021). Users of the app reported being more exposed to negative incidents online during the study period (F(2,1591) = 3.94, p =.020). The frequency of cyberbullying decreased during the study period, but among all study participants, including those who had not used the app. The findings provide valuable insight into whether mobile apps can function as preventive and supportive self-help resources in reducing the harmful effects of cyberbullying and negative online incidents on mental health outcomes among adolescents.